The experiences of people living with HIV/AIDS in Gaborone, Botswana: Stigma, its consequences and coping mechanisms - Vincent Setlhare; Anne Wright; Ian Couper (South African Family Practice, 2014)
Background: This study was carried out in Bontleng, Extension 14 and Old Naledi, which are low-income residential areas of Gaborone, Botswana. The aim of the study was to explore the experiences of people living with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS). The study was an attempt to discover the experience of the lives of people living with HIV/AIDS (PLWHA) and how they coped living with the infection.